Analysis and validation of a CFD-DPM method for simulating dust suppression sprays. (19th May 2022) - Roberts, Jon; Wypych, Peter; Hastie, David; Liao, Rongfu
Abstract: Predicting the performance of finely atomized sprays used for airborne dust suppression is an important aspect in ensuring workers are properly protected from harmful dust emissions in the industries that rely on bulk materials handling and processing. It is well known that finely atomized sprays are effective for airborne dust capture, however there is less understanding of the best methods for predicting spray dispersion especially in adverse conditions, such as when exposed to high cross-winds. This study aims to evaluate the ability for CFD to be used in the prediction of spray performance in applications relating to airborne dust suppression. An Eulerian-Lagrangian approach is evaluated against available experimental data of sprays operating in quiescent conditions and with a perpendicularly applied cross-wind. Varying levels of agreement have been achieved based on a given set of input parameters: prediction of spray velocity was found to be within 20% of measured values, droplet size was within 13% and mist penetration within 10%. The results demonstrate the potential for CFD to be practically applied in the design of dust suppression systems, especially in regard to mist penetration or reach, which is one of the primary concerns when selecting appropriate nozzle designs and operating parameters.